Acute sacral nerve stimulation reduces visceral mechanosensitivity in Rat through spinal opioid pathway. Issue 6 (25th March 2015) - Langlois, L.; Meleine, M.; Ouelaa, W.; Caremel, R.; Bridoux, V.; Benard, M.; Dechelotte, P.; Ducrotte, P.; Grise, P.; Leroi, A. M.; Gourcerol, G.
Abstract Background Sacral nerve stimulation (SNS) is an alternative surgical treatment of refractory urge incontinence and/or fecal incontinence. Despite its clinical efficacy, the mechanisms of action of SNS remain poorly understood. The aim of this experimental study was to evaluate the effect of SNS on visceral mechanosensitivity in rats. Methods Anesthetized Sprague–Dawley rats were treated with SNS or sham stimulation. SNS was performed by implanting an electrode close to the sacral nerve root S1. Rats were administered either a non‐selective opioid receptor antagonist (naloxone) or a nitric oxide synthase inhibitor (L‐NAME). Colonic mechanosensitivity was evaluated using the variation of arterial blood pressure as a spino‐bulbar reflex in response to graded isobaric colorectal distension (CRD). C‐fos immunoreactive neurons were quantified in spinal and supraspinal sites. μ‐opioid receptor (MOR) internalization was counted in the sacral spinal cord with sham or effective SNS in response to CRD. Key Results SNS reduced visceral mechanosensitivity in response to CRD. This effect was reversed by intrathecal and intraveinous naloxone administration. In both models, CRD induced increased c‐fos immunoreactivity in the dorsal horn neurons of the sacral spinal cord and supraspinal areas. This increase was prevented by SNS. MOR internalization was significantly higher in stimulated group. Conclusions & Inferences SNS impacts on visceral mechanosensitivity by decreasing the spino‐bulbar reflex in response to CRD. Spinal opioid receptors are likely involved in this effect.